Surveillance of Aedes aegypti (Diptera: Culicidae) and COVID-19 in Cuba: General Considerations - María del Carmen Marquetti Fernández; Andrés Bisset Marquetti (Open Journal of Tropical Medicine - Peertechz Publications, 2020)
The Pan American Health Organization (PAHO) has emphasized the need to maintain efforts to prevent, detect, and treat vector-borne diseases during the COVID-19 pandemic since the combined impact of both could have potentially devastating consequences on the population at risk. Cuba during the COVID-19 pandemic established its protocol for its combat, respecting the provisions of the World Health Organization (WHO) and adding other internal measures in the country that have ensured its effective control. Parallel to the epidemic, the country continues to monitor and control of Aedes aegypti to avoid a possible dengue epidemic. This article provides some considerations that must be taken into account in the presence of COVID-19 and dengue cases that contribute to the strengthening of effective and rapid surveillance and control of Ae. aegypti.